Failure Analysis of Polypropylene Fiber Reinforced Concrete Two-Way Slabs Subjected to Static and Impact Load Induced by Free Falling Mass - Al-Rousan,Rajai Z. (2018)
Abstract The impact resistance of concrete is considered as poor due to a relatively energy dissipating characteristics and tensile strength. Therefore, this paper investigates the feasibility of using polypropylene fibers (PF) to enhance punching shear capacity of reinforced concrete (RC) two-way slabs subjected to drop-weight impacts. The evaluated parameters included two slab thickness (70 mm and 90 mm), five different PF percentages (0%, 0.3%, 0.6%, 0.9%, and 1.2%), and two impact load height (1.2 m and 2.4 m). The tested slabs divided into three groups: not subjected to impact load, subjected to impact load at a height of 1.2 m, and subjected to impact load at a height of 2.4 m, resulting in a total of 25 slabs. The behavior of each two-way RC slab was evaluated in terms of the crack patterns, ultimate punching shear capacity. The present experimental data can be used for further assessment of the performance of PF reinforced concretes two-way slabs as well as providing a well-documented dataset related to the impact-resistant applications which is presently limited within the literature. The results showed that adding the PF at a dosage of 0.3 to 1.2% by volume of concrete and increasing the slab thickness from 70 mm to 90 mm leads to considerable enhancement in the overall structural behavior of the slabs and their resistance to impact loading. Interestingly, the degradation in the ultimate punching capacity of the slabs subjected to impact load at a height of 1.2 and 2.4 m is 30.5% and 34.6%, respectively. Finally, an empirical model was proposed for predicting the punching shear capacity of RC two-way slabs based on reliable experimental results available in literature